Valorization of apple pomace: Structural and rheological characterization of low-Methoxyl Pectins extracted with green agents of citric acid/sodium citrate - Rui Guo; Rong Fan; Jiaxuan Hu; Xinyue Zhang; Lin Han; Min Wang; Caian He (Food Chemistry: X)
Traditional production of low-methoxyl pectin (LMP) is labor-intensive and environmentally harmful. This study explores using citric acid/sodium citrate as a green extractant for valorizing LMPs from apple pomace. Two types of pectin, AP-5 and AP-8, were extracted at pH 5.0 and 8.0, resulting in LMPs with methoxylation degrees of 42.33 % and 34.68 %, respectively. Monosaccharide composition and SEC-MALLS analysis revealed that APs are rich in arabinose side chains and contain heterogeneous fractions, while FTIR spectra confirmed their low-methoxyl structure. Compared to the commercial low-methoxyl pectin, APs exhibited higher critical pH but lower critical Ca2+ levels for acid- and Ca2+-induced gels, where hydrogen bonding and electrostatic interactions were the dominant intermolecular forces. Notably, AP-8 and AP-5 demonstrated superior stability in acid- and Ca2+-induced gels. Additionally, combined acidic and Ca2+ conditions enhanced the gel strength and stability of APs. These findings highlight the potential of APs in developing novel, particularly low-calorie, food products.